ANALISIS DETERMINAN PERINGKAT OBLIGASI PADA PERUSAHAAN NON LEMBAGA KEUANGAN DI INDONESIA OLEH PT. PEFINDO - Muhammad Hafiz (2021)
This study aims to determine the effect of profitability measured by return on asset (ROA), leverage measured by the debt to equity ratio (DER) and company size measured by the regular logarithm of total assets (SIZE) on bond ratings as measured by ordinal scale in non-financial institution companies in Indonesia by PT. Pefindo in the 2017-2019 research year. The population in this study were all non-financial institutions listed on the Indonesia Stock Exchange, totaling 111 companies. The number of samples used in this study were 36 companies selected using purposive sampling method. The analysis technique used is Panel Data Regression Analysis with Microsoft Excel 2010 and E-Views 10 with a significance level of 5%. The results showed (1) profitability had a positive effect on bond ratings, (2) leverage had no effect on bond ratings, and (3) company size had no effect on bond ratings.